The influence of an electrical impedance tomography belt on lung function determined by spirometry in sitting position - Zhang, Na; Jiang, Hongying; Zhang, Chenxi; Li, Qing; Li, Yi; Zhang, Bin; Deng, Jia; Niu, Guangyu; Yang, Bo; Frerichs, Inez; Moeller, Knut; Fu, Feng; et al. (Physiological measurement, 2020)
Objective: The aim of the study was to examine whether an electrical impedance tomography (EIT) electrode belt changed the lung function in healthy volunteers and patients with respiratory muscle weakness (RMW) and chronic obstructive pulmonary disease (COPD). Approach: In total, thirty subjects were included (10 healthy volunteers, 10 subjects with RMW, maximum inspiratory pressure < 40 cmH2O, and 10 COPD, grade I-IV). Spirometry measurements were conducted in a sitting position once a day at similar times on two consecutive days. Slow expiratory vital capacity (VC), forced vital capacity (FVC) and maximum voluntary ventilation (MVV) manoeuvres were performed. On day 1, spirometry was performed without the EIT electrode belt, and on day 2, the belt was attached to the thorax. Main results: Lung function was not influenced by the electrode belt in healthy subjects. The test-retest reliability in the healthy group was 0.89, 0.89 and 0.85 for VC, FVC and MVV, respectively. On the other hand, all investigated parameters were significantly decreased in the RMW group (VC, 51.3 ± 18.0 versus 46.5 ± 18.0% predicted, without versus with EIT belt, p< 0.01; FVC, 51.7 ± 19.0 versus 45.8 ± 18.1% predicted, p< 0.01; MVV, 41.0 ± 20.0 versus 38.8 ± 19.6% predicted, p< 0.01). VC and MVV also decreased significantly in the COPD group (VC, 77.4 ± 20.5 versus 74.6 ± 18.8% predicted, p< 0.05; MVV, 57.4 ± 15.7 versus 54.4 ± 12.5% predicted, p< 0.05). Significance: An EIT electrode belt could reduce lung volumes in subjects with pre-existing lung diseases. Comparing lung function acquired with an electrode belt to corresponding values obtained without the belt should be avoided.